Mengenal Ulumul Qur’an: Kunci Memahami Wahyu: Penelitian - Muhyi, Abdul; Raya, Ahmad Thib (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
This article introduces Ulumul Qur’an as a discipline that serves as the key to comprehensively understanding the revelation of the Qur’an. The discussion covers the main scope—such as asbāb al‑nuzūl, qirā’āt, nasikh‑mansukh, the history of the compilation of the mushaf, and methodologies of tafsir—as well as the role of this field in bridging historical, linguistic, and legal contexts. With a concise and communicative approach, the article highlights the practical benefits of studying Ulumul Qur’an for general readers, students, and dakwah practitioners, while also emphasizing the importance of scholarly study to prevent misinterpretations in exegesis.